THE SHARP EDGES OF CONTEMPORARY WORLD POLITICS - I. V. Bocharnikov (Vestnik MGIMO-Universiteta, 2018)
Book Review: Bulavin A.V., Karpovich O.G., Manoilo A.V., Mantusov V. B. World politics. Advanced lines and red lines. Moscow: RIO Russian customs Academy, 2018. 456 p.The article presents a detailed review of the monograph “World politics. Front lines and red lines”. The author assesses the nature and content of the influence of the main participants in the system of international relations, both individual States and non-state actors, including transnational corporations on the state and prospects of development of world politics. Directions of adjustment of the foreign policy strategy of Russia in the conditions of aggravation of a situation and reanimation of hostile anti-Russian course from a number of participants of world political process are defined.